Stable chromosomal association of MSL2 defines a dosage-compensated nuclear compartment. - Straub, T.; Neumann, M.F.; Prestel, M.; Kremmer, E.; Kaether, C.; Haass, C.; Becker, P.B. (Chromosoma, 2005)
Dosage compensation in Drosophila is controlled by a complex (DCC) of proteins and noncoding RNA that binds specifically to the male X chromosome and leads to fine-tuning of transcription. Here, we employ male SL2 cells to characterize DCC function and dynamics during steady state of dosage compensation. Knocking down the key regulator of dosage compensation, male-specific-lethal 2 (MSL2), leads to loss of propagation of histone H4 lysine 16 acetylation and of the twofold elevation of transcription characteristic of the compensated male X chromosome. Surprisingly, lack of dosage compensation does not impair cell viability. Targeting of MSL2 to a reporter gene suffices to initiate dosage compensation in the cell model. Using photobleaching techniques in living cells, we found the association of MSL2 with the X chromosome to be exceptionally stable, essentially excluding dynamic redistribution of the DCC during interphase. This immobility distinguishes MSL2 from most other chromosomal proteins. Our findings have profound implications for the mechanism underlying dosage compensation and furthermore provide a new, conceptual reference of stability in an otherwise highly dynamic nuclear environment.